Development of a Procurement-4.0-PMS using the Balanced Scorecard - Lorenzo Pirrone; Dennis Meyer (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Performance measurement systems (PMS) are multidimensional, indicator-based systems that form the basis for performance evaluation and management. In management research and in corporate practice, the Balanced Scorecard (BSC) is the most established PMS. In principle, the BSC can also be used in Procurement, but there is a lack of studies on its suitability or adaptation in digitalized Procurement 4.0. To close this gap, this paper develops an initial concept of a PMS geared to Procurement 4.0 with help of the BSC. Methodology: For data collection, a systematic literature review is conducted according to Durach et al. (2017). The results will be systematized in the development of a general Procurement-BSC and taken into account in the adaptation of the model to Procurement 4.0. Subsequently, the model will be validated by expert interviews. Findings: The results show that the holistic performance evaluation of Procurement 4.0 will become even more important in the future. As part of its new understanding, the BSC supports the development of Procurement into a value and strategy driver of the organization. Originality: To the best of the authors' knowledge, this is the first study of its kind. As such, it represents the starting point for further research.
urn:nbn:de:gbv:830-882.0161979; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Innovation management; technology management